2011
DOI: 10.5761/atcs.oa.09.01502
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Results of Completion Pneumonectomy

Abstract: Purpose: We report our experience with completion pneumonectomy (CP). Methods: We report on operative procedure and morbidity, mortality, and survival rates. Results: CP was performed for malignancy in 12 patients and postoperative complications after the first operation in 4 patients. Intrapericardial dissection of vessels was performed in 14 patients (87.5%). Partial vertebrectomy from the second to the fifth vertebrae was performed in 1 patient. Carinal resection was performed in 2 patients. Morbidity inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
3
8
3
Order By: Relevance
“…Although the rate of complications in the completion pneumonectomy group was high (80.9%), it did not influence postoperative mortality. The difference between the complication rate observed in this study and that reported by other authors (30-62%) may stem from the fact that the analysis of the cited authors included only selected, mostly severe complications [ 11 15 ]. The present study considered all observed complications, including postoperative anemia requiring the transfusion of blood (23.8%) or arterial pressure drops requiring catecholamine therapy (33.3%).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Although the rate of complications in the completion pneumonectomy group was high (80.9%), it did not influence postoperative mortality. The difference between the complication rate observed in this study and that reported by other authors (30-62%) may stem from the fact that the analysis of the cited authors included only selected, mostly severe complications [ 11 15 ]. The present study considered all observed complications, including postoperative anemia requiring the transfusion of blood (23.8%) or arterial pressure drops requiring catecholamine therapy (33.3%).…”
Section: Discussioncontrasting
confidence: 81%
“…Although it is not a randomized prospective study, but only a retrospective analysis, it may still shed light on the efficacy and safety of each of the analyzed treatment methods. The number of surgically treated patients in the study group is low ( n = 21), but similar rates of completion pneumonectomy are reported by authors from other centers, where the number of analyzed cases rarely exceeds 50 [ 7 , 10 , 11 ]. They point to the fact that in most patients with recurrent lung cancer, there are contraindications for repeat surgery (recurrence location precluding radical procedures, mediastinal lymph node involvement, high operative risk associated with concomitant disorders, results of functional tests disqualifying the patient from pneumonectomy).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…(1, 2, 13) Despite this knowledge, bronchial stump reinforcement with a pedicled flap or coverage with adjacent tissue is not universally employed. (1, 4, 13-15) For our series, a relatively uniform technique was employed. Five of the 6 participating surgeons have been trained at our institution and the 6 th surgeon (GAP) has been the mentor at our program for over 20 years.…”
Section: Commentmentioning
confidence: 99%